The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1074/jbc.r113.472936
|View full text |Cite
|
Sign up to set email alerts
|

Peroxynitrite, a Stealthy Biological Oxidant

Abstract: Peroxynitrite is the product of the diffusion-controlled reaction of nitric oxide and superoxide radicals. Peroxynitrite, a reactive short-lived peroxide with a pK a of 6.8, is a good oxidant and nucleophile. It also yields secondary free radical intermediates such as nitrogen dioxide and carbonate radicals. Much of nitric oxide-and superoxide-dependent cytotoxicity resides on peroxynitrite, which affects mitochondrial function and triggers cell death via oxidation and nitration reactions. Peroxynitrite is an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
462
1
9

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 701 publications
(478 citation statements)
references
References 100 publications
6
462
1
9
Order By: Relevance
“…As studies impressively demonstrated: superoxide is able to kill bacteria directly, especially when the virulence of the pathogen is dramatically attenuated (i.e. by superoxide dismutase deficiency) [46] [47]. Here in this study, the inhibition of specific glutamine-dependent pathways were one important constituent in the significant turnaround of the pyruvate-induced alterations in the immune parameters examined.…”
Section: Pyruvate Induced Effects: Is There An Impact By Adding a Glumentioning
confidence: 70%
“…As studies impressively demonstrated: superoxide is able to kill bacteria directly, especially when the virulence of the pathogen is dramatically attenuated (i.e. by superoxide dismutase deficiency) [46] [47]. Here in this study, the inhibition of specific glutamine-dependent pathways were one important constituent in the significant turnaround of the pyruvate-induced alterations in the immune parameters examined.…”
Section: Pyruvate Induced Effects: Is There An Impact By Adding a Glumentioning
confidence: 70%
“…The term cytokine storm is used to accommodate the observation that multiple excessive inflammatory causes can induce excessive release of inflammation factors like interleukin-1, interleukin-6, interleukin-12, tumor necrosis factor-α, interferon-α, interferon-β, interferon-γ, Monocyte Chemoattractant Protein-1 and interleukin-8 thereby leading to a disease that appears similar to sepsis [30,31]. Importantly, excessive inflammation reactions can also induce acute oxidative stress [2]. Together, both cytokine storm and oxidative stress promote each other and induce MODS, result in high mortality rate [15].…”
Section: Influenza and Other Severe Viral Infectionsmentioning
confidence: 99%
“…In the past decade, molecular hydrogen was considered a surprising agent, which can significantly reduce oxidative stress by selectively reducing hydroxyl radical Hutaohong2010@163.com (•OH) and Peroxynitrite (ONOO-) [1,[8][9][10]. It has recently been revealed that hydrogen can both down-regulate expression of oxidative-related genes and pro-inflammatory cytokine genes directly and indirectly [2][3][4][5]11,12]. Oxidative stress and systemic inflammatory response syndrome have been confirmed to play critical roles in tissue and organ damages after polymicrobial sepsis injury, acute peritonitis injury, and peritonitis, which can develop into lethal sepsis with inappropriate treatment [13,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that all-trans-retinoic acid induced nNOS expression through activation of the phosphatidylinositol 3-kinase (PI3K)/Akt signaling pathway and the orphan nuclear receptor DAX1 (NR0B1). All-trans-retinoic acid, among other retinoids, as for example, 9-cis-retinoic acid, are originated from vitamin A intake in vivo (Napoli 1996(Napoli , 1999(Napoli , 2012, and increased access to retinoids may lead to an increased expression of nNOS and augmented rates of NO production, which favors increased production of peroxynitrite (ONOO -), a reactive specie that give rise to nitryl cation (NO 2 + ), nitrogen diozide radical ( l NO 2 ), and hydroxyl radical ( l OH) through a reaction called homolytic fission (Radi 2013, Carballal et al 2014. In spite of this evidences, the effects of vitamin A supplementation on NOS enzyme activity and expression in the mammalian brain remain to be investigated.…”
Section: Molecular Evidences Of Vitamin A-related Neurotoxicitymentioning
confidence: 99%